Advantages and Disadvantages of Investor-State Dispute Settlement through Arbitration - Simonyan, Ani (Bulletin of Yerevan University C: Jurisprudence, 2022)
The article is dedicated to the very contemporary issues of State-investor disputes, which are mainly in commercial locality. This article will try to explore both positive and negative sides of dispute settlement in the international investment law through arbitration. The critical and reproving views of the arbitration process will be analyzed. Several international expert group evaluative reports will be presented in this research. State-investor commercial dispute settlement problems will also be examined in the light of ICSID platform.
Keywords: Investor-State dispute; arbitration; ISDS; ISCID; investment law; investment dispute; arbitrator; London Court of International Arbitration; arbitral system; investment treaty